Erythrocyte Sensitivity to Hypertonic Cryohemolysis in Different Animals - Denisova, O. N.; Ramazanov, V. V.; Zhegunov, G. F. (Problems of Cryobiology and Cryomedicine, 2004)
Hypertonic cryohemolysis of bovine, canine and equine erythrocytes was investigated. It was found-out, that the erythrocyte sensitivity to the damaging factors, pH medium and anion channel inhibitors had its peculiarities. The peculiarities of erythrocyte behavior are discussed in respect of different transport systems and membrane composition.